Новые клещи-фитосейиды Крыма (Parasitiformes, Phytoseiidae). Сообщение I - Колодочка, Л.А. (Вестник зоологии, 1981)
Data on the habitat and distribution are presented for 15 Phytoseiidae species which were not previously registered in the Crimea. A description and drawings of the new for science species Amblyseius jailensis sp. n. are given.